Assessing Artificial Recharge on Groundwater Quantity Using Wells Recharge - Waqed H. Hassan; Zainab N. Ghazi (Civil Engineering Journal, 2023)
In arid and semi-arid countries like Iraq, which suffer from water scarcity due to the effects of climate change and decreased surface water flow, groundwater is considered a vital source of irrigation water. This study is concerned with the influence of artificial recharge on the rehabilitation of the unconfined aquifer called Al-Dibdibba, located between the cities of Najaf and Kerbala in central Iraq around 31°550′ N and 32°450′ N and 43°300′ E and 44°300′ E. Due to excessive groundwater pumping rates for irrigation, this aquifer has suffered from groundwater decline and increased salinization during the previous 20 years. By establishing a conceptual model in the groundwater modeling system software (GMS), a numerical model was made to simulate groundwater flow. Artificial recharge using recycled water (tertiary treatment) from Kerbala's primary WWTP was carried out using 25 injection wells. The model was calibrated against historical and observed water level data for periods from 2016 to 2017. Three scenarios to predict how the aquifer would act with artificial recharge of 5%, 8%, and 10% from the total daily outflow of the WWTP in Kerbala (100000 m3/day) were studied. The calibration model met the observed values of groundwater levels with R2 = 0.989 for steady-state simulations and R2 = 0.987 for transient simulations. In the final analysis of the simulation, the results show that the maximum predicted groundwater level was raised by the injection of treated water through 25 wells by 1.05 m for 5000 m3/day, 2 m for 8000 m3/day, and 3 m for 10,000 m3/day recharge pumping rates. In addition, if water were pumped into the aquifer, it might support the development of agricultural lands covering more than 93 km2. So, artificial recharge can be considered one of the important solutions to adaptation to the effects of climate change and desertification in Iraq. Doi: 10.28991/CEJ-2023-09-09-010 Full Text: PDF